The characteristics teaching materials of biology laboratory management - Saifuddin, Much Fuad; Puspitasari, Etika Dyah (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2021)
The suitable teaching materials will make it easier for students to learn in the classroom. To present suitable teaching materials, a needs analysis is needed. This study aimed to determine the types and characteristics of teaching materials needed in learning biology laboratory management. The survey method was carried out to students who were randomly selected. The instrument is arranged in the form of a questionnaire by paying attention to each characteristic indicator of various teaching materials. The validity of the instrument used a combination of expert judgment. The questionnaire is distributed via google form to students who have taken laboratory management courses with a filling period of 2 weeks obtained 123 respondents. The data were analyzed descriptively of quantitatively and qualitatively. The results showed that the percentage of students who needed teaching materials for biology laboratory management lectures was 98%; the characteristics of teaching materials wanted by students included: containing learning objectives, using simple language, sequenced materials according to lecture sessions, containing summaries, and providing feedback. Teaching materials based on existing characteristics can be in the form of modules that are adapted to the Semester Learning Plan.